Things beyond resemblance : collected essays on Theodor W. Adorno - Hullot-Kentor, Robert (Columbia themes in philosophy, social criticism, and the arts., 2006)
Theodor W. Adorno was a major twentieth-century philosopher and social critic whose writings on oppositional culture in art, music, and literature increasingly stand at the center of contemporary intellectual debate. In this excellent collection, Robert Hullot-Kentor, widely regarded as the most distinguished American translator and commentator on Adorno, gathers together sixteen essays he has written about the philosopher over the past twenty years. The opening essay, ""Origin Is the Goal, "" pursues Adorno's thesis of the dialectic of enlightenment to better understand the urgen